2014
DOI: 10.1111/dth.12177
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose acitretin in Papillon-Lefèvre syndrome: treatment and 1-year follow-up

Abstract: The Papillon-Lefèvre syndrome (PLS) is a rare, autosomal recessive disease that manifests with palmoplantar keratoderma and destructive periodontitis resulting in early onset periodontal breakdown in deciduous and permanent dentition. Management of this condition is difficult. Here we report one 11-year-old consanguineous Muslim boy suffering from PLS. After failing to get any benefit from methotrexate, three cycles of acitretin, each for 2 months, were given 1 month apart. In each cycle, acitretin (25 mg) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The favorable therapeutic response of skin lesions to oral acitretin and isotretinoin in our patients has previously been documented . Our report of six patients and a novel mutation in CTSC gene further expands the broad phenotypic and genotypic spectrum of PLS, which should be considered in patients presenting with the combination of PPK and severe early‐onset periodontitis.…”
Section: Discussionsupporting
confidence: 69%
“…The favorable therapeutic response of skin lesions to oral acitretin and isotretinoin in our patients has previously been documented . Our report of six patients and a novel mutation in CTSC gene further expands the broad phenotypic and genotypic spectrum of PLS, which should be considered in patients presenting with the combination of PPK and severe early‐onset periodontitis.…”
Section: Discussionsupporting
confidence: 69%
“…The ready availability of large volumes of urine gives it many advantages over saliva and gingival crevicular fluids, which contain only small amounts of CatC activity in healthy subjects . The early implementation of a strict oral hygiene regimen can minimize the progression of periodontitis, and oral retinoid therapy can clear the skin lesions and improve the quality of life of patients with PLS . Demonstrating the absence of urinary CatC activity soon after birth and before the onset of clinical symptoms can be used as a screening procedure for PLS in populations with a high frequency of intrafamilial marriages and in close relatives of PLS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the variant form, involving the loricrin gene (loricrin hPPK) low‐dose isotretinoin has been described to prevent digital amputation 18. Etretinate, isotretinoin and low‐dose acitretin have been the most important therapeutic options for keratoderma in Papillon–Lefèvre syndrome (PLS), an autosomal recessive hPPK associated with periodontitis caused by mutations in the Cathepsin C ( CTSC ) gene, with generally good results in terms of efficacy 19. In PLS, Balestri et al 20.…”
Section: Resultsmentioning
confidence: 99%
“…18 Etretinate, isotretinoin and low-dose acitretin have been the most important therapeutic options for keratoderma in Papillon-Lef evre syndrome (PLS), an autosomal recessive hPPK associated with periodontitis caused by mutations in the Cathepsin C (CTSC) gene, with generally good results in terms of efficacy. 19 In PLS, Balestri et al 20 showed a worsening of hPPK despite longterm treatment with acitretin (25 mg daily for 62 months). Acitretin was switched to 10 mg of alitretinoin for 2 weeks followed by 30 mg daily.…”
Section: Systemic Treatmentsmentioning
confidence: 99%